The Perceived Role of Others in Facilitating or Impeding Healing from Substance Abuse - Palmer, Roma S.; Daniluk, Judith C. (Canadian Journal of Counselling and Psychotherapy, 2008)
The purpose of this qualitative, phenomenological study was to examine the subjective experiences of six recovering addicts as they reflected on how their interactions with others facilitated or impeded their healing from addiction. The study involved in-depthinterviews with six participants who had recovered from their extensive substance abuse histories. Seven themes common to all participants included losses/gains, support/discouragement,understanding/misunderstanding, belonging/not belonging, meaning/meaninglessness, hope/hopelessness, and negative/positive perceptions of self and others. Implications for counselling addicts during the recovery process are discussed based on these findings.